The Influence of Green Marketing, Environmental Awareness, and Consumer Value on Sustainable Purchase Intentions - Wulandjani, Harimurti; Akbari, Deni Adha; Arniwita, Arniwita; Mayratih, Siska; Purwaningsih, Nining; Sudarmanto, Eko (Westscience Press, 2025)
This study examines the influence of green marketing, environmental awareness, and consumer values on sustainable purchasing intentions in Indonesia. Using a quantitative approach with a sample size of 150 respondents, data were collected via a Likert scale (1-5) and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) software. The findings reveal that all three constructs significantly and positively influence sustainable purchasing intentions, with environmental awareness emerging as the strongest determinant. Green marketing initiatives effectively enhance consumer trust, while consumer values play a critical role in aligning ethical consumption with purchasing behaviors. The study underscores the importance of integrating environmental awareness campaigns and value-driven marketing strategies to promote sustainable consumption in Indonesia. Recommendations for businesses and policymakers are provided to further advance sustainable practices in the region.